2021
DOI: 10.1080/17535069.2021.1904276
|View full text |Cite
|
Sign up to set email alerts
|

Discourses and practices of the smart city in Central Eastern Europe: insights from Hungary’s ‘big’ cities

Abstract: This paper intends to fill a gap in critical smart city scholarship regarding the Central Eastern European (CEE) context. To this end, smart city understandings and practices in Hungary's five (noncapital) major cities are examined through a discourse-analytical focus on relevant municipal planning documents, existing interventions and key actors' interpretations. The paper concludes that although smart city building in Hungary in many ways aligns with trends in the Global North and South, there are also notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
(104 reference statements)
0
4
0
1
Order By: Relevance
“…How the national and local politics of urban smart projects actually take shape in practice could be an important indicator for determining the degree to which the smart city concept is being implemented in a given country or city. Recent studies on the implementation of smart city projects in Central and Eastern Europe (Nicula et al, 2022; Sikora‐Fernandez, 2018; Varro & Szalai, 2022) have demonstrated that much progress needs to be made in order to reach the desired goal of including marginal people into genuinely smart cities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…How the national and local politics of urban smart projects actually take shape in practice could be an important indicator for determining the degree to which the smart city concept is being implemented in a given country or city. Recent studies on the implementation of smart city projects in Central and Eastern Europe (Nicula et al, 2022; Sikora‐Fernandez, 2018; Varro & Szalai, 2022) have demonstrated that much progress needs to be made in order to reach the desired goal of including marginal people into genuinely smart cities.…”
Section: Discussionmentioning
confidence: 99%
“…The governance of smart cities and urban smart city projects in CEE cities is an under‐researched topic (McElroy, 2020; Nicula et al, 2022; Sikora‐Fernandez, 2018; Varro & Szalai, 2022). Taking the case of the Roma people from the outskirts of the city of Cluj‐Napoca (Romania's third‐largest city), Erin McElroy (2020) claims that the Roma have suffered a double dispossession, in which not only have ‘digital nomads’ indulged technocapitalist fantasies by appropriating Roma identity, but also the Roma have been evicted to make way for the coming of Western digital nomads and IT companies.…”
Section: Smart City: Concept Projects and Spacementioning
confidence: 99%
See 1 more Smart Citation
“…A kormányzás megjelenése releváns 9-19 százalékos reprezentációval bír a modellhalmazok egymás közötti viszonyrendszerében, ami azonban az e-kormányzás tényleges működéséről keveset árul el. Több magyar nagyváros okossá válását nehezíti ugyanis az érintett lakosság, a civil szféra részvételének és kezdeménye-zéseinek gyengesége, illetve az, hogy a vonatkozó stratégiai célok gyakorlatba való átültetésében feloldhatatlan korlátot jelent a városvezetés és a helyi társadalom együttműködési mechanizmusainak hiánya (Varró, Szalai 2021).…”
Section: A Modell Reprezentációja Az Elemzett Városok Esetébenunclassified
“…Moreover, there is not only a lack of research on the climate governance of mid-sized cities but also on post-socialist cities (Ferenčuhová 2020). Existing studies on post-socialist cities have rather focused on somewhat related topics such as green spaces (Badiu et al 2019;Csomós et al 2021), sustainability (Svirčić Gotovac and Kerbler 2019), or smart cities (Sikora-Fernandez 2018;Varró and Szalai 2021). Moreover, there is also a lack of studies on the regions (Länder) of the former German Democratic Republic (GDR).…”
Section: Introductionmentioning
confidence: 99%